Atom bond connectivity index of molecular graphs of alkenes and cycloalkenes - Mohammed, Mohanad A.; Mohd Atan, Kamel Ariffin; Khalaf, A. M.; Hasni, Roslan; Md. Said, Mohamad Rushdan; Nawawi @ Mohamed Nawawi, Athirah (American Scientific Publishers, 2017)
The atom-bond connectivity (ABC) index is one of the recently most investigated degree based molecular structure descriptors that have applications in chemistry. For a graph G, the ABC index is defined as ABC(G) = ∑ uv∈E(G) √[d v + du – 2]/[d v · d u ], where du denotes the degree of a vertex u in G. In this paper, we establish the general formulas for the atom bond connectivity index of molecular graphs of alkenes and cycloalkenes.